THEORETICAL AND PRACTICAL ASPECTS OF POLYSEMY IN LEGAL TRANSLATION - NOWAK-KORCZ, Paulina (Comparative Legilinguistics, 2015)
The objective of this paper is to illustrate the phenomenon of polysemy in Polish and French legal language. The first part of the article deals with the definition of polysemy. In the second part, the author focuses her attention on polysemy in legal translation. The distinction between linguistic and legal polysemy (polysémie linguistique, polysémie juridique) is also presented (Sourioux, Lerat 1975). The examples of polysemic words with their multiple meanings have been indicated.